2019
DOI: 10.1186/s12882-018-1156-2
|View full text |Cite
|
Sign up to set email alerts
|

Validating laboratory defined chronic kidney disease in the electronic health record for patients in primary care

Abstract: BackgroundElectronic health record (EHR) data is increasingly used to identify patients with chronic kidney disease (CKD). EHR queries used to capture CKD status, identify comorbid conditions, measure awareness by providers, and track adherence to guideline-concordant processes of care have not been validated.MethodsWe extracted EHR data for primary-care patients with two eGFRcreat 15-59 mL/min/1.73 m^2 at least 90 days apart. Two nephrologists manually reviewed a random sample of 50 charts to determine CKD st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 22 publications
1
17
0
Order By: Relevance
“…A recent methodological study reported that documentation of ICD diagnostic codes is a relatively good surrogate for PCP awareness 7 . In a recent cross-sectional observational study, only 47% of patients with lab evidence of CKD in primary care had CKD diagnosis in the chart 7 .…”
Section: Discussionmentioning
confidence: 99%
“…A recent methodological study reported that documentation of ICD diagnostic codes is a relatively good surrogate for PCP awareness 7 . In a recent cross-sectional observational study, only 47% of patients with lab evidence of CKD in primary care had CKD diagnosis in the chart 7 .…”
Section: Discussionmentioning
confidence: 99%
“…We used University of California, San Francisco (UCSF) electronic medical records (EMR) data to identify a cohort of persons with CKD in primary care as previously described. 5 We defined CKD as two eGFR measurements between 15 and < 60 ml/min/1.73 m 2 at least 3 months apart. 6 This study was approved by the institutional review board at UCSF.…”
Section: Methodsmentioning
confidence: 99%
“…Covariates included patient demographics, comorbidities, insurance type, and number of primary care visits, as previously described. 5 We compared characteristics by patient language preference (English vs. non-English) using chi-squared tests. We estimated the relative risk of each outcome for patients with non-English language preference compared with English-language preference using multivariable modified Poisson regression models with logarithm link, clustered on provider and adjusting for potential confounders.…”
Section: Methodsmentioning
confidence: 99%
“…This is consistent with data from a recent methodological study that demonstrated that 68% of patients deemed to have CKD based on historic eGFRs had confirmed CKD determined by physician chart review. 44 Many potentially eligible patients in our study had experienced repeated episodes of acute kidney injury or had false-positive dipstick albuminuria results.…”
Section: Discussionmentioning
confidence: 99%